Oral Etoposide for Platinum-Resistant and Recurrent Epithelial Ovarian Cancer: a Study by the Anatolian Society of Medical Oncology - Kucukoner, Mehmet; Isikdogan, Abdurrahman; Yaman, Sebnem; Gumusay, Ozge; Unal, Olcun; Ulas, Arife; Buyukberber, Suleyman (Asian Pacific Organization Cancer Prevention, 2012)
Background: The aim of this study was to evaluate the efficacy and toxicity of long-term, low-dose oral etoposide as an advanced treatment option in patients with platinum resistant epithelial ovarian cancer. Materials and Methods: For the purposes of this study, 51 patients with histologically-confirmed, recurrent or metastatic platinum-resistant epithelial ovarian cancer (EOC) treated at six different centers between January 2006 and January 2011 were retrospectively evaluated. Patients were treated with oral etoposide (50 mg/day for a cycle of 14 days, repeated every 21 days). Results: Among the 51 platinum-resistant patients, 17.6% demonstrated a partial response and 25.5% a stable response. The median progression-free survival (PFS) was 3.9 months (95% CI, 2.1-5.7), while the median overall survival was 16.4 months (11.8-20.9). No significant relationship was observed between the pre-treatment CA 125 levels, post-treatment CA-125 levels and the treatment response rates (p=0.21). Among the 51 patients who were evaluated in terms of toxicity, grade 1 or 4 hematologic toxicity was observed in 19 (37.3%); and grade 1-4 gastrointestinal toxicity occurred in 15 patients (29.4%). Conclusions: Chronic low-dose oral etoposide treatment is generally effective and well-tolerated in platinum-resistant ovarian cancer patients.
Keywords: Ovarian cancer; oral etoposide; toxicity; PFS